EFFICIENCY ANALYSIS OF BANK BUMN BUKU EMPAT AND ITS DETERMINANT IN INDONESIA - Nasution, Sahruddin; Siregar, Hermanto; Novianti, Tanti (Universitas Brawijaya, Indonesia, 2020)
Efficiency is an important indicator needed by a bank to survive in tight competition, change in consumer behavior, and increase economic cooperation among countries. The objective of this study was to analyze the efficiency of BUMN Bank of BUKU Empat and its determinants. The method used to analyze the efficiency was the Data Envelopment Analysis (DEA) by Variable Return to Scale (VRS) Approach. Besides, the analysis of its determinants used Data Panel regression. During the research periods, several findings were provided. Firstly, Bank BRI has resulted in the highest score of efficiency. Secondly, the results of data panel regression suggested that Loan to Deposit Ratio (LDR), the share of the deposit (PDPK), Return on Asset (ROA), Exchange Rate (ER), and GDP Growth (GDP) were positively related to. Capital Adequacy Ratio (CAR), Total Asset (TA), and Inflation (INF) were negatively related. The future studies suggested to use a more extended data period and compared with banks in countries that have the same economic character.